Football matches as natural experiments: Exploring wastewater quality parameters for dynamic population normalization in sub-sewersheds - Schmiege Dennis; Haertel Christoph; Schmidt Tina; Tuerk Jochen; Moebus Susanne (Water Research, 2026)

From QTL to candidate genes: a data-driven approach to unravel the genetic architecture of yellow rust resistance in central European wheat - Jiaojiao Wang; Renate H. Schmidt; Guoliang Li; Albrecht Serfling; Jochen C. Reif; Yong Jiang (Theoretical and Applied Genetics, 2026)
Key message A data mining strategy capitalizing on high-resolution SNP information, sequence variant annotation and QTL information from three populations facilitated an efficient nomination of candidate genes for YR resistance, supported by Yr27 and functional annotations. Abstract Genome-wide association studies (GWAS) have become routine in many crops, but the prioritization of candidate genes remains challenging. Here, we developed a new approach to identify environment-specific quantitative trait loci (QTL) using GWAS and analyzed 5,840 wheat genotypes distributed over three experimental populations, including 5,243 single-cross hybrids and 597 elite lines. Resequencing the parental genotypes identified over 640,000 single-nucleotide polymorphisms (SNPs) after filtering. The hybrid panels were tested in 19 environments for susceptibility to Puccinia striiformis f. sp. tritici ( Pst ), a pathogen responsible for severe yellow rust (YR) epidemics especially after 2012. QTL patterns in diverse environments showed substantial differences, reflecting spatial and temporal dynamics. Combining high-resolution SNP information, sequence variant annotation and QTL information from different populations obtained via a novel GWAS approach enabled the efficient nomination of candidate genes for YR resistance loci of particular relevance for Central European wheat. The power of the developed strategy for mining data from different experimental populations was demonstrated as the validated resistance gene Yr27 was identified as sole candidate gene for one QTL region.

Wheat variety mixtures enhance yield stability and result in pronounced overyielding for certain line combinations - Malte Victor Schmidt; Yusheng Zhao; Valentin Hinterberger; Sandra Lorena Zapata Martinez; Andreas Maurer; Jochen Christoph Reif; Samira El Hanafi (European Journal of Agronomy, 2026)

Reconsidering palliative radiotherapy in addition to PD-1 blockade for non-small cell lung cancer: results from the FORCE phase II trial (AIO/YMO-TRK-0415) - Farastuk Bozorgmehr; Inn Chung; Jürgen R. Fischer; Marc Bischof; Akin Atmaca; Sophie Wetzel; Martin Faehling; Dirk Bottke; Martin Wermke; Esther G. C. Troost; Cornelia Kropf-Sanchen; Thomas Wiegel; et al. (Clinical & Experimental Metastasis, 2025)
Introduction of immune checkpoint inhibitors (ICI) has improved overall survival (OS) for advanced non-small cell lung cancer (NSCLC). However, responses differ greatly amongst patients. Additional radiotherapy (RT) may promote tumor-specific immunity and synergize with ICI to improve tumor control. The multicenter phase II FORCE trial evaluated safety and efficacy of nivolumab with additional palliative radiotherapy (5 × 4 Gy) as clinically indicated in pre-treated metastatic non-squamous NSCLC (group A, n = 41), including pretreated patients without an indication for radiotherapy in a parallel cohort as real-world controls (group B, n = 60). With an objective response rate (ORR) of 8.3% in group A ( n = 41), the primary endpoint was not met ( p = 0.991). ORR in group B ( n = 60) was 23.8%. Patient characteristics indicated a significantly poorer baseline clinical condition for group A compared to B, including worse Eastern Cooperative Oncology Group (ECOG) performance status (PS, p = 0.020) and more metastatic sites ( p = 0.009). Consequently, group A had shorter progression-free survival (median PFS, 1.9 versus 3.7 months, hazard ratio [HR] 1.69 [95% CI (1.10, 2.58)]) and OS (median 6.0 versus 12.6 months, HR 1.75 [95% CI (1.07, 2.84)]). In multivariable analyses for the intention-to-treat (ITT) population, ORR, PFS and OS were inversely associated with the patients’ ECOG PS (ORR odds ratio [OR] 0.126, p = 0.004) and correlated positively with tumor PD-L1 expression (ORR OR 12.8, p = 0.022), but not with radiotherapy administration ( p = 0.169–0.854). Adverse events were distributed equally in both groups. Addition of palliative radiotherapy to nivolumab was safe and feasible, but not associated with improved efficacy. Patients with an indication for palliative radiotherapy have an inherently worse prognosis which cannot be overcome by radiation-induced immunostimulation. Clinical features and PD-L1 expression influence clinical outcomes more than radiotherapy administration and should be considered when evaluating the effectiveness of immuno-/radiotherapy combinations. ClinicalTrials.gov identifier : NCT03044626

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Effect-directed analysis of endocrine and neurotoxic effects in stormwater depending discharges - Nicolai Baetz; Jorge Ricardo Cunha; Fabian Itzel; Torsten C. Schmidt; Jochen Tuerk (Water Research, 2024)

Modelling of dynamic mastication physics of cheese/casein gels as function of milk-fat distribution and intensity of thermo-mechanical treatment - Dominic Oppen; Florian Schmidt; Sarah Helena Braitmaier; Jörg Hinrichs; Jochen Weiss (Food Research International, 2024)

Flowability of plant based food powders: Almond, chestnut, chickpea, coconut, hazelnut and rice - Björn Düsenberg; Jochen Schmidt; Ikay Sensoy; Andreas Bück (Journal of Food Engineering, 2023)

Impact of weathered multi-walled carbon nanotubes on the epithelial cells of the intestinal tract in the freshwater grazers Lymnaea stagnalis and Rhithrogena semicolorata - Katrin Weise; Thomas Kurth; Anna Schmidt; Carola Winkelmann; Jochen Becker; Susanne Kretschmar; Thomas Ulrich Berendonk; Dirk Jungmann (Environmental Science and Pollution Research, 2023)
Freshwater grazers are suitable organisms to investigate the fate of environmental pollutants, such as weathered multi-walled carbon nanotubes (wMWCNTs). One key process is the uptake of ingested materials into digestive or absorptive cells. To address this, we investigated the localization of wMWCNTs in the intestinal tracts of the mud snail Lymnaea stagnalis ( L. stagnalis ) and the mayfly Rhithrogena semicolorata ( R. semicolorata ). In L. stagnalis , bundles of wMWCNTs could be detected in the midgut lumen, whereas only single wMWCNTs could be detected in the lumina of the digestive gland. Intracellular uptake of wMWCNTs was detected by transmission electron microscopy (TEM) but was restricted to the cells of the digestive gland. In larvae of R. semicolorata , irritations of the microvilli and damages in the apical parts of the epithelial gut cells were detected after feeding with 1 to 10 mg/L wMWCNTs. In both models, we detected fibrillar structures in close association with the epithelial cells that formed peritrophic membranes (PMs). The PM may cause a reduced transmission of wMWCNT bundles into the epithelium by forming a filter barrier and potentially protecting the cells from the wMWCNTs. As a result, the uptake of wMWCNTs into cells is rare in mud snails and may not occur at all in mayfly larvae. In addition, we monitor physiological markers such as levels of glycogen or triglycerides and the RNA/DNA ratio. This ratio was significantly affected in L. stagnalis after 24 days with 10 mg/L wMWCNTs, but not in R. semicolorata after 28 days and 10 mg/L wMWCNTs. However, significant effects on the energy status of R. semicolorata were analysed after 28 days of exposure to 1 mg/L wMWCNTs. Furthermore, we observed a significant reduction of phagosomes per enterocyte cell in mayfly larvae at a concentration of 10 mg/L wMWCNTs ( p < 0.01).

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Planning and governing nature-based solutions in river landscapes: Concepts, cases, and insights - Christian Albert; Jochen Hack; Stefan Schmidt; Barbara Schröter (Ambio, 2021)
Nature-based solutions (NBS), understood as actions that use ecosystem processes to address societal needs, can play important roles to future-proof river landscape development for people and nature. However, knowledge gaps exist how NBS can be planned and implemented at landscape scales. This Special Issue brings together insights and experiences from studies of assessing, planning, and implementing NBS in river landscapes in Europe and beyond. It addresses three research fields: (i) NBS effects, looking at the effectiveness of NBS to achieve ecological, social, and/or economic outcomes, (ii) NBS planning, focusing on approaches for planning and designing NBS, and (iii) NBS governance, relating to governance and business models for implementation. The twelve contributions deliver evidence on how NBS outperform conventional, rather technical solutions, provide guidance and tools to operationalize the NBS concept into practice, and showcase successful governance models of NBS in different contexts. The editorial ends with an outlook on further research needs.

Klärung des spezifischen Korrosionsverhaltens von mikroporigen Chromüberzugssystemen in CaCl2-Elektrolyten - Christof Langer; Wolf Wendland; Kai Honold; Lukas Schmidt; Jochen S. Gutmann; Michael Dornbusch (BHM Berg- und Hüttenmännische Monatshefte, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

BacHBerry: BACterial Hosts for production of Bioactive phenolics from bERRY fruits - Alexey Dudnik; A. Filipa Almeida; Ricardo Andrade; Barbara Avila; Pilar Bañados; Diane Barbay; Jean-Etienne Bassard; Mounir Benkoulouche; Michael Bott; Adelaide Braga; Dario Breitel; Rex Brennan; et al. (Phytochemistry Reviews, 2018)

Recent advances in cured raw ham manufacture - Ramona Bosse (née Danz); Anne Müller; Monika Gibis; Agnes Weiss; Herbert Schmidt; Jochen Weiss (Critical Reviews in Food Science and Nutrition, 2018)

Extracting genotype information of Arabidopsis thaliana recombinant inbred lines from transcript profiles established with high-density oligonucleotide arrays - Renate Schmidt; Anastassia Boudichevskaia; Hieu Xuan Cao; Sang He; Rhonda Christiane Meyer; Jochen Christoph Reif (Plant Cell Reports, 2017)

The disorganized visual cortex in reelin-deficient mice is functional and allows for enhanced plasticity - Justyna Pielecka-Fortuna; Robin Jan Wagener; Ann-Kristin Martens; Bianka Goetze; Karl-Friedrich Schmidt; Jochen F. Staiger; Siegrid Löwel (Brain Structure and Function, 2015)

A new Dominican amber fossil of the derived fern genus Pleopeltis confirms generic stasis in the epiphytic fern diversity of the West Indies - Harald Schneider; Alexander R. Schmidt; Paul C. Nascimbene; Jochen Heinrichs (Organisms Diversity & Evolution, 2015)

The Bromeliaceae tank dweller Bromeliophila (Lejeuneaceae, Porellales) is a member of the Cyclolejeunea-Prionolejeunea clade - Jochen Heinrichs; Aleksandra Czumaj; Shanshan Dong; Armin Scheben; Alfons Schäfer-Verwimp; Denilson F. Peralta; Kathrin Feldberg; Alexander R. Schmidt; Harald Schneider (Plant Systematics and Evolution, 2014)

Exploring the impact of fossil constraints on the divergence time estimates of derived liverworts - Kathrin Feldberg; Jochen Heinrichs; Alexander R. Schmidt; Jiří Váňa; Harald Schneider (Plant Systematics and Evolution, 2013)

Epidermal growth factor-induced modulation of cytokeratin expression levels influences the morphological phenotype of head and neck squamous cell carcinoma cells - Galina Makarova; Michael Bette; Ansgar Schmidt; Ralf Jacob; Chengzhong Cai; Fiona Rodepeter; Thomas Betz; Johannes Sitterberg; Udo Bakowsky; Roland Moll; Andreas Neff; Andreas Sesterhenn; et al. (Cell and Tissue Research, 2013)

Quantitative multi-risk analysis for natural hazards: a framework for multi-risk modelling - Jochen Schmidt; Iain Matcham; Stefan Reese; Andrew King; Rob Bell; Roddy Henderson; Graeme Smart; Jim Cousins; Warwick Smith; Dave Heron (Natural Hazards, 2011)

Inputs of Nutrients and Fecal Bacteria to Freshwaters from Irrigated Agriculture: Case Studies in Australia and New Zealand - Robert J. Wilcock; David Nash; Jochen Schmidt; Scott T. Larned; Mark R. Rivers; Pat Feehan (Environmental Management, 2011)

Finding appropriate reference sites in large-scale aquatic field experiments - Susanne I. Schmidt; Marie König-Rinke; Katja Kornek; Carola Winkelmann; Markus A. Wetzel; Jochen H. E. Koop; Jürgen Benndorf (Aquatic Ecology, 2009)

Expression profiling of metabolic genes in response to methyl jasmonate reveals regulation of genes of primary and secondary sulfur-related pathways in Arabidopsis thaliana - Ricarda Jost; Lothar Altschmied; Elke Bloem; Jochen Bogs; Jonathan Gershenzon; Urs Hähnel; Robert Hänsch; Tanja Hartmann; Stanislav Kopriva; Cordula Kruse; Ralf R. Mendel; Jutta Papenbrock; et al. (Photosynthesis Research, 2005)

Kinetics of absorbance and anisotropy upon excited state relaxation in the reaction center core complex of a green sulfur bacterium - Sieglinde Neerken; Ying-Zhong Ma; Jochen Aschenbrücker; Kristiane A. Schmidt; Frank R. Nowak; Hjalmar P. Permentier; Thijs J. Aartsma; Tomas Gillbro; Jan Amesz (Photosynthesis Research, 2000)